2000
DOI: 10.1159/000013601
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cardiac Calcinosis in Hemodialysis Patients by Whole-Body Scintigraphy with 99m-Technetium Methylene Diphosphonate

Abstract: A noninvasive method for the diagnosis of cardiac calcinosis, a life-threatening complication in hemodialysis patients with end-stage renal disease (ESRD), has not, as yet, been firmly established. We tested whether whole body scanning with 99m-technetium methylene diphosphonate (MDP) might visualize cardiac calcinosis. In 19 consecutive chronic hemodialysis ESRD patients (13 males and 6 females, aged 40–81, mean 63 ± 8 years) with cardiovascular disease [mitral annular calcinosis and/or calcified aortic valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
2
4
0
1
Order By: Relevance
“…In our study, only single measurement of PTH level was made, which might explain the inconsistent result with Grandaliano. However, there were several studies reporting a negative association between PTH levels and cardiac calcification, calcific aortic stenosis, and peripheral vascular disease among dialysis patients, which was supporting our findings (20,36,37). The reason for the negative association might be related to deposition of calcium at extraskeletal sites, preferentially in low-bone turnover states.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, only single measurement of PTH level was made, which might explain the inconsistent result with Grandaliano. However, there were several studies reporting a negative association between PTH levels and cardiac calcification, calcific aortic stenosis, and peripheral vascular disease among dialysis patients, which was supporting our findings (20,36,37). The reason for the negative association might be related to deposition of calcium at extraskeletal sites, preferentially in low-bone turnover states.…”
Section: Discussionsupporting
confidence: 90%
“…This is the first study to evaluate the consequences of isolated myocardial calcification independent of any structural alterations of the vascular system. Our results may be clinically relevant especially for understanding the cardiovascular abnormalities and risks in the dialysis population, because both vascular and myocardial calcifications are highly prevalent in this patient group (11)(12)(13)(14)(15). This potential relevance is further supported by previous observations that patients on dialysis show decreased serum fetuin-A levels and that fetuin-A deficiency in uremia is associated with impaired cardiovascular survival (9).…”
Section: Discussionsupporting
confidence: 76%
“…It has even been postulated that dystrophic calcification might contribute to cardiac dysfunction with at least the same prevalence as ischemic heart disease (10). In dialysis patients, the magnitude of cardiovascular calcification is especially high, affecting atherosclerotic plaques, arterial media, cardiac valves, and the myocardium, respectively (11)(12)(13)(14)(15). The severity of medial calcification is associated with arterial stiffness and increased pulse wave velocity (16).…”
mentioning
confidence: 99%
“…SHPT was traditionally considered as an important factor for cardiovascular morbidity and mortality of ESRD patients [ 11 ]. Though certain previous studies reported negative associations between PTH levels and CV morbidity [ 12 , 13 ], it was considered that low PTH levels represented residual confounding by nutritional status [ 14 ]. Parathyroidectomy (PTX) is the main treatment for severe SHP refractory to medical treatment.…”
Section: Introductionmentioning
confidence: 99%